2022
DOI: 10.3390/coatings12091301
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Multi-Track Laser-Cladding Process of Titanium Alloy Based on RSM and NSGA-II Algorithm

Abstract: Titanium alloy is an important material in the 21st century and its consumption in the aerospace and energy fields is increasing. In the production and repair of titanium alloy, the problem of energy saving and consumption reduction is becoming increasingly important. Laser-cladding technology with optimized parameters can bring great economic benefit. In order to obtain the best process parameters of laser-cladding TC4 alloy powder, a method of laser-cladding parameters’ optimization based on the RSM and NSGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…From Figure 1, it can be observed that all four groups of laser-cladded layers exhibit obvious WC particles and slight defects. Additionally, there is a distinct bright band at the interface between the laser-cladded layer and the heataffected zone (HAZ), where the laser-cladded layer exhibits a smooth and continuous surface contour line with minimal amounts of slag [28,29], indicating a good metallurgical bond between the laser-cladded layer and the substrate. continuous surface contour line with minimal amounts of slag [28,29], indicating a good metallurgical bond between the laser-cladded layer and the substrate.…”
Section: Microstructurementioning
confidence: 99%
“…From Figure 1, it can be observed that all four groups of laser-cladded layers exhibit obvious WC particles and slight defects. Additionally, there is a distinct bright band at the interface between the laser-cladded layer and the heataffected zone (HAZ), where the laser-cladded layer exhibits a smooth and continuous surface contour line with minimal amounts of slag [28,29], indicating a good metallurgical bond between the laser-cladded layer and the substrate. continuous surface contour line with minimal amounts of slag [28,29], indicating a good metallurgical bond between the laser-cladded layer and the substrate.…”
Section: Microstructurementioning
confidence: 99%
“…2 The cladding layer is influenced by process parameters such as cladding powder, powder feeding rate, scanning speed, and laser power. 3,4 Harsh and demanding environments can induce structural damage, thermal impairment, and corrosion failure in the cladding layer. 5 The IN625 powder belongs to the Ni-Cr-Fe series alloy, a nickel-based alloy, and the laser cladding layer possesses exceptional high-temperature strength, corrosion resistance, oxidation resistance, and deformation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…2 The cladding layer is influenced by process parameters such as cladding powder, powder feeding rate, scanning speed, and laser power. 3,4 Harsh and demanding environments can induce structural damage, thermal impairment, and corrosion failure in the cladding layer. 5…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloy has the mechanical properties of low density, high specific strength, high specific modulus, corrosion resistance and non-magnetic. Recently, titanium alloys have been adopted as a substitute for structural steel in the construction of aircraft parts such as bulkheads, slide rails, landing gear beams, fans, compressor discs and blades [1,2]. Moreover, due to the high specific fracture toughness, good medium and low temperature toughness and high melting point, titanium alloys are also extensively used in the manufacturing of various accessories of aero-engine casings, such as cups, double hinges, anti-icing shells and afterburner impellers of fuel systems, etc.…”
Section: Introductionmentioning
confidence: 99%